Strategic Analysis of Executive Competencies and Human Resource Development in the Kaliwatu Group, Batu Tourism City, East Java - Meidiaputri, Riza Dwi; Soetjipto, Budi Eko; Syihabudin, Syihabudin (International Journal of Economics Development Research (IJEDR), 2025)
This research analyze the skills of staff and the human resource development strategy approaches at Kaliwatu Group, a top adventure tourism company in Bumiaji District, Batu, East Java. The study identifies employee knowledge, skills, and attitudes (KSAs), especially concerning whitewater rafting protocols specified in the Indonesian National Work Competency Standards (SKKNI) No. 62/2009 and No. 60/2024. This study utilizes a qualitative approach that includes interviews, site observations, and competency evaluations. Although most executive team members possess solid knowledge of operations, safety practices, and customer service, there are still gaps in advanced tourism management and regulation updates. The group's human resource strategy actively incorporates internal and external training, certification initiatives, and peer learning. Nevertheless, hiring tends to favour passion over formal qualifications or certifications, leading to inconsistencies in service quality. The results underscore the urgent need for ongoing, structured professional development to close existing competency voids, improve staff performance, and provide sustainable, high-quality tourism services. Suggestions involve enhancing training programs, aligning more closely with national criteria, expanding knowledge-sharing networks among local tourism experts, and collaborating with the local community.